Joint and independent associations of dietary vitamin intake and prevalence of cardiovascular disease in chronic kidney disease subjects: a cross-sectional analysis - Guoqing Wang; Guoqing Wang; Luojun Huang; Luojun Huang; Wenwen Yue; Wenwen Yue; Jun Feng; Jun Feng (Frontiers in Nutrition)
BackgroundCurrently, the joint and independent effects of intake of multiple dietary vitamins (including vitamin A, B1, B2, B6, B12, C, D, E, and K) on the prevalence of cardiovascular disease (CVD) in the chronic kidney disease (CKD) population are unclear, so this study was conducted to investigate mainly this point.MethodsWe collected National Health and Nutrition Examination Survey (NHANES) data from 2011 to 2016. We performed weighted multivariate logistic regression models to analyze the association of single dietary vitamins intake with CVD. Additionally, we examined the co-exposure of nine dietary vitamins, defined as their concurrent intake, and evaluated the potential additive or interactive effects of co-exposure of nine dietary vitamins on CVD risk in CKD patients using Bayesian kernel machine regression (BKMR) and weighted quantile sum (WQS) regression.ResultsFinally, 2,203 CKD participants (weighted n = 27,120,429) were included, and 622 had CVD, with a CVD prevalence of 28.2%. In the fully adjusted model, by comparing the third tertile with the first tertile, the adjusted OR [T3 vs. T1] for the effect of vitamin B6 on CVD prevalence was 0.67 (95% CI, 0.51–0.89, p-value = 0.01), while that of vitamin E was 0.61 (95% CI, 0.42–0.87, p-value = 0.01). In the WQS model, the intake of nine dietary vitamins was negatively correlated with CVD prevalence (OR: 0.81, 95% CI: 0.70–0.93, p-value = 0.004). In the BKMR model, when the concentration was between the 25th and 75th percentiles, there was an overall negative correlation between the total intake of nine dietary vitamins and CVD prevalence.ConclusionHigh intakes of vitamin B6 and vitamin E were associated with low CVD risk in CKD patients, respectively. Additionally, nine dietary vitamins (vitamins A, B1, B2, B6, B12, C, D, E, and K) co-exposure were inversely correlated with the CVD prevalence in the CKD populations.